A new genus of cricket near to Miogryllus and Kazuemba from the Colombian Atlantic coast and the first report of Gryllodes sigillatus from Colombia (Orthoptera: Gryllidae: Gryllinae: Modicogryllini) - Cadena-Castañeda, Oscar J. (Zootaxa, 2011)
Faguagryllus luteolus n. gen. et n. sp., from the Colombian Atlantic coast is described and illustrated. The relation with the genera Miogryllus Saussure, 1877 and Kazuemba Mello, 1990 is discussed; as well as their inclusion in Modicogryllini. Gryllodes sigillatus is reported for Colombia, with distribution data of the examined specimens, and the allocation of figures of Gryllodes species in Otte 2006 is corrected.